Effect of Nitrogen on Cellular Production and Release of the Neurotoxin Anatoxin-A in a Nitrogen-Fixing Cyanobacterium - Gagnon, Alexis; Pick, Frances R. (Frontiers in Microbiology, 2012)
Anatoxin-a (ANTX) is a neurotoxin produced by several freshwater cyanobacteria and implicated in lethal poisonings of domesticated animals and wildlife. The factors leading to its production in nature and in culture are not well understood. Resource availability may influence its cellular production as suggested by the carbon-nutrient hypothesis, which links the amount of secondary metabolites produced by plants or microbes to the relative abundance of nutrients. We tested the effects of nitrogen supply on ANTX production and release in a toxic strain of the cyanobacterium Aphanizomenon issatschenkoi (Nostocales). We hypothesized that nitrogen deficiency might constrain the production of ANTX. However, the total concentration and more significantly the cellular content of anatoxin-a peaked (max. 146 µg/L and 1683 µg•g-1 dry weight) at intermediate levels of nitrogen supply when N-deficiency was evident based on phycocyanin to chlorophyll a and carbon to nitrogen ratios. The results suggest that the cellular production of anatoxin-a may be stimulated by moderate nutrient stress as described recently for another cyanotoxin (microcystin).